The Effect of Exclusive Breastfeeding on Hospital Stay and Morbidity due to Various Diseases in Infants under 6 Months of Age: A Prospective Observational Study - Amarpreet Kaur; Karnail Singh; M. S. Pannu; Palwinder Singh; Neeraj Sehgal; Rupinderjeet Kaur (International Journal of Pediatrics)
Background. Mother’s milk is the best for the babies. Protective and preventive role of breast milk was evaluated in this study by assessing the relation of type of feeding and duration of hospital stay or morbidity. Methods. This prospective study was conducted in a tertiary care hospital and 232 infants in the age group of 14 weeks to 6 months formed the sample. There are two groups of infants, that is, one for breastfed and one for top fed infants. Statistical analysis was done and results were calculated up to 95% to 99% level of significance to find effect of feeding pattern on hospital stay due to various diseases and morbidity. Results. Prolonged hospital stay, that is, >7 days, was lesser in breastfed infants and results were statistically significant in case of gastroenteritis (p value < 0.001), bronchopneumonia (p value = 0.0012), bronchiolitis (p value = 0.005), otitis media (p value = 0.003), and skin diseases (p value = 0.047). Lesser morbidity was seen in breastfed infants with gastroenteritis (p value 0.0414), bronchopneumonia (p value 0.03705), bronchiolitis (p value 0.036706), meningitis (p value 0.043), and septicemia (p value 0.04). Conclusions. Breastfed infants have shorter hospital stay and lesser morbidity in regard to various diseases as compared to top fed infants.